Exenatide decreases liver fat content and epicardial adipose tissue in patients with obesity and type 2 diabetes: a prospective randomized clinical trial using magnetic resonance imaging and spectroscopy. Issue 9 (31st May 2016) - Dutour, A.; Abdesselam, I.; Ancel, P.; Kober, F.; Mrad, G.; Darmon, P.; Ronsin, O.; Pradel, V.; Lesavre, N.; Martin, J. C.; Jacquier, A.; Lefur, Y.; et al.
Abstract : Aim: To conduct a prospective randomized trial to investigate the effect of glucagon‐like peptide‐1 (GLP‐1) analogues on ectopic fat stores. Methods: A total of 44 obese subjects with type 2 diabetes uncontrolled on oral antidiabetic drugs were randomly assigned to receive exenatide or reference treatment according to French guidelines. Epicardial adipose tissue (EAT), myocardial triglyceride content (MTGC), hepatic triglyceride content (HTGC) and pancreatic triglyceride content (PTGC) were assessed 45 min after a standardized meal with 3T magnetic resonance imaging and proton magnetic resonance spectroscopy before and after 26 weeks of treatment. Results: The study population had a mean glycated haemoglobin (HbA1c) level of 7.5 ± 0.2% and a mean body mass index of 36.1 ± 1.1 kg/m 2 . Ninety five percent had hepatic steatosis at baseline (HTGC ≥ 5.6%). Exenatide and reference treatment led to a similar improvement in HbA1c (−0.7 ± 0.3% vs. −0.7 ± 0.4%; p = 0.29), whereas significant weight loss was observed only in the exenatide group (−5.5 ± 1.2 kg vs. −0.2 ± 0.8 kg; p = 0.001 for the difference between groups). Exenatide induced a significant reduction in EAT (−8.8 ± 2.1%) and HTGC (−23.8 ± 9.5%), compared with the reference treatment (EAT: −1.2 ± 1.6%, p = 0.003; HTGC: +12.5 ± 9.6%, p = 0.007). No significant difference was observed in other ectopic fat stores, PTGC or MTGC. In the group treated with exenatide, reductions in liver fat and EAT were not associated with homeostatic model assessment of insulin resistance index, adiponectin, HbA1c or fructosamin change, but were significantly related to weight loss (r = 0.47, p = 0.03, and r = 0.50, p = 0.018, respectively). Conclusion: Our data indicate that exenatide is an effective treatment to reduce liver fat content and epicardial fat in obese patients with type 2 diabetes, and these effects are mainly weight loss dependent.